Identificação de obstáculos a um maior crescimento do transporte ferro-rodoviário de cargas unitizadas no Brasil e apresentação de medidas para sua superação - Dores, Adely Maria Branquinho das (2018)
This research aims to identify the obstacles to a greater use of rail/road multimodal transport of unitized load in Brazil, alternatively to road transport, and to present suggestions for overcoming them. It investigates the evolution of American, European and Brazilian regulation, as well as the development of rail/road multimodal transport in these countries, in order to identify possible deficiencies in Brazilian regulatory/institutional model. Concurrently, applying the AHP (Analytic Hierarchy Process), it hierarchizes several variables related to the choice of shippers and transport operators of the transport mode and defines a model for comparison of containerized load transportation alternatives, based on the costs of the hierarchical variables. It applies the developed model in a Case Study, which conclusions are compared with those of the regulatory/institutional evaluation. The research concludes with the identification of regulatory/institutional deficiencies and suggestions to overcome them.